Linking omics and ecophysiology in Eucalytus: unravelling stress tolerance in a forest species - Correia, Barbara dos Santos (2017)
Eucalyptus plantations are among the most productive forest stands worldwide. In Portugal and Spain, they are widely used for pulp production and as an energy crop. However, the region’s Mediterranean climate, with increasingly severe summer drought, negatively affects eucalypt growth and increases mortality. The aim of this doctoral thesis was to unravel drought tolerance in Eucalyptus globulus by investigating and interconnecting information on the processes mediating water deficit and rehydration, from gene and molecular regulation to physiological responses and plant performance, using two different genotypes and different stress trials. The thesis disclosed herein is presented in a series of research papers (chapters 2, 3, 4 and 5), preceded by a general introduction (chapter 1) and closed with concluding remarks (chapter 6). Chapter 2 describes a greenhouse trial and a slowly imposed water deficit, and is divided into three subchapters. Two genotypes (AL-18 and AL-10) were submitted to a 3-week water stress period at two different intensities (18% and 25% of field capacity), followed by 1 week of rewatering. Recovery was assessed 1 day and 1 week after rehydration. Several phytohormones were monitored in leaves, xylem sap and roots, 2 h, 4 h, 24 h, and 168 h after rewatering. Water deficit reduced height, biomass, water potential, and gas exchange. Contrarily, the levels of pigments, chlorophyll fluorescence parameters and MDA increased. ABA and ABA-GE levels increased, and JA content decreased in leaves and increased in xylem sap. During recovery, most of the physiological and biochemical responses of stressed plants were reversed. Comparative proteome (using difference gel electrophoresis) and metabolome (using gas chromatography–mass spectrometry) analyses enabled the separation and isolation of 2031 peptide spots, 217 of which were identified, and the detection of 121 polar metabolites. The analysis of the resilient clone AL-18, which presented a response network very distinct from the responsive clone AL-10, reinforced the role of specific photosynthetic and defence-related proteins as key players in mediating drought tolerance and revealed new players: glutamine synthetase, malate dehydrogenase and isoflavone reductase-like protein. Chapter 3 regards a climate chamber trial and a sudden water shortage, and is divided in two subchapters. The relative expression of 12 transcripts was analysed by quantitative PCR in two clones with different degrees of tolerance (AL-18 and AL-13) 7 and 11 days after water withholding and rehydration (2 h and 3 days after rewatering). Sudden water shortage was more detrimental to the plants than when slowly imposed, with heavier outcomes in clone AL-13, including plant death. Potential molecular indicators linked to enhanced water stress tolerance in Eucalyptus globulus were identified: rubisco activase (RCA), ferredoxin-NADP(H) oxireductase (FNR), mitochondrial malate dehydrogenase (mMDH), peroxisomal catalase (CAT) and isoflavone reductase (IFR). Afterwards, several biochemical markers of oxidative stress and DNA methylation patterns were quantified in the leaves of AL-18. The alterations detected using global and specific indicators reflected the parallel induction of redox and complex DNA methylation changes occurring during stress imposition and relief. Chapter 4 reports a field trial: the previously identified set of indicators for selection of water stress tolerance was tested in field-grown AL-18 and AL-13. Some of the plants were irrigated (IR), and others were left under environmental conditions of reduced rainfall (NI) during six and a half weeks prior to rewatering. Clone AL-18 showed few fluctuations in the conditions tested, and the alterations found in clone AL-13 highlighted an induction of photosynthetic and photorespiration metabolism after artificial rehydration. The results corroborated that responses to field conditions cannot be extrapolated from a stress applied individually in the context of developing selection markers. Chapter 5 describes a climate chamber trial that tested the isolated and combined effect of drought and heat. Physiological, biochemical and metabolomic alterations were monitored in AL-18 after a 5-day of consistent drought and/or 4 h at 40ºC. Testing drought-stressed plants subject to a heat shock revealed a decrease in gas exchange, Ψpd and JA, no alterations in electrolyte leakage, MDA, starch and pigments and increased glutathione pool in relation to control. The induction of cinnamate was a novel response triggered only by the combined stress. These results highlighted that the combination of drought and heat provides significant protection from more detrimental effects of drought-stressed eucalypts, confirming that combined stresses alter plant metabolism in a novel manner that cannot be extrapolated by the sum of the different stresses applied individually. This thesis describes a number of biological responses that enable E. globulus to thrive under conditions of water deficit and provides useful information of pathways to be explored in order to find suitable markers of abiotic stress tolerance in this species. Despite that, a bigger challenge remains and consists of the need to focus our studies in more realistic, field-like experiments, at least in the context of finding suitable selection markers in the climate change era.